Classification Of Tests And Testing Equipment (Eurasian Journal of Research, Development and Innovation, 2025)
The article presents their classifications as the main information provided on the condition of the product based on the test results. When determining the classification, the quality of the choice of the program, methods and testing tools is taken into account, that is, the quality of the project, ideology, tests and related technical solutions, as well as the quality of the implementation of the chosen testing methodology, that is, the quality of the implementation of programs and methods